Corn Yield Response to Water Availability - T. Newell; K. Roozeboom; G. J. Kluitenberg; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2015)
Drought-tolerant technologies have become popular in hybrids for low-yielding corn environments across central and western Kansas and are marketed for their ability to produce higher grain yields with less water. The objective of this study was to compare water use, yield, and water use efficiency (WUE) of two types of drought-tolerant (DT) corn hybrids and a high-yielding non-DT hybrid. Water use and yield of two DT and one non-DT, high-yielding hybrid were compared in both dryland and irrigated situations. The average yield for the irrigated corn was 217 bu/a, and the average was 127 bu/a in dryland, representing a yield increase of 90 bu/a. The irrigated corn received a total of 10 in. more water than the dryland corn over the course of the growing season, resulting in 9 bu for each additional inch of water use averaged across the three hybrids. The irrigated corn used a mean of 20.85 in. of water, and the dryland corn used a mean of 11.66 in. of water. The WUE was 10.71 bu/in. and 10.43 bu/in. for dryland and irrigated corn, respectively. Although hybrid yields differed in the irrigated environment, water use and WUE were similar for all hybrids in both dryland and irrigated environments. One DT hybrid exhibited more stable yields across dryland and irrigated environments compared with the other DT hybrid and the non-DT hybrid.
Keywords: corn; water use; yield; water use efficiency; drought tolerance